Causal Aspects of Social Capital of Iranian Patients with Cancer: Evidence of Predictive, Modifying and Descriptive Effects in Health Inequality. - Mohamad Tavakol; Mohsen Naserirad (Tehran University of Medical Sciences, 2013)
There is a good literature confirming the effects of social capital on different health domains. The increase in different types of cancer has caused scientists to encounter a number of issues regarding the reasons of affliction by this disease. The aim of this empirical research was to study the causal aspects of social capital of Iranian patients with cancer.The study was a causal-comparative study conducted in the spring and summer of 2010 in Tehran. The sample consists of 212 people selected based on affliction or no affliction to cancer. Social capital emphasizes two dimensions of structure and cognition. Social participation, social trust and sense of social solidarity are considered as different dimensions of social capital. The focus has been on personal social capital.The effect and association of social capital are not significant with any of stomach and colon cancers. The effect and association of social trust are not significant with any of stomach, colon and breast cancers.People with similar social capital in their life have different experiences of cancer-related stress and unhealthy behaviors. Thus a specific feature of a stressful social determinant is not a reliable criterion to determine the degree of stress and the extent of its effect on affliction to cancer.